2006
DOI: 10.1042/bj20051964
|View full text |Cite
|
Sign up to set email alerts
|

Misincorporation of free m-tyrosine into cellular proteins: a potential cytotoxic mechanism for oxidized amino acids

Abstract: In vitro studies demonstrate that the hydroxyl radical converts L-phenylalanine into m-tyrosine, an unnatural isomer of L-tyrosine. Quantification of m-tyrosine has been widely used as an index of oxidative damage in tissue proteins. However, the possibility that m-tyrosine might be generated oxidatively from free L-phenylalanine that could subsequently be incorporated into proteins as an L-tyrosine analogue has received little attention. In the present study, we demonstrate that free m-tyrosine is toxic to cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 33 publications
4
74
2
1
Order By: Relevance
“…However, because significant growth inhibition is observed at Ͼ100-fold lower concentrations in Arabidopsis than in B. subtilis (23) or Chinese hamster ovary cells (24), plant proteins would have to be uniquely sensitive to m-tyrosine incorporation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because significant growth inhibition is observed at Ͼ100-fold lower concentrations in Arabidopsis than in B. subtilis (23) or Chinese hamster ovary cells (24), plant proteins would have to be uniquely sensitive to m-tyrosine incorporation.…”
Section: Resultsmentioning
confidence: 99%
“…m-Tyrosine is incorporated into proteins in place of phenylalanine in bacteria (23) and mammalian cells (24), where it is associated with increased protein turnover (25). Vigna radiata (mung bean) phenylalanine tRNA synthase accepts m-tyrosine with 25% of the efficiency of phenylalanine (26), suggesting that m-tyrosine might also be misincorporated into plant proteins.…”
Section: Resultsmentioning
confidence: 99%
“…As a mechanism of cytotoxicity, misincorporation of m-tyrosine in place of phenylalanine into cellular protein was suggested in bacteria 37) and cultured Chinese-hamster ovary cells. 38) Plant amino acids having anti-microbial and insecticidal activities revealed that one mechanism of toxicity was the incorporation of non-protein amino acids into the cellular protein of predators; however, the biosynthetic incorporation of m-tyrosine into plant systems has not been well studied. Mung bean phenylalanine tRNA synthase accepts m-tyrosine with 25% efficiency of phenylalanine, suggesting that m-tyrosine might also be misincorporated into plant proteins; a small amount of m-tyrosine was detected from the root protein of m-tyrosine-treated Arabidopsis seedlings.…”
Section: Phytotoxic Activity and Action Mechanism Of M-tyrosinementioning
confidence: 99%
“…There is evidence that in protein synthesis, mtyrosine is incorporated in bacteria instead of phenylalanine (Aronson e Wermus, 1965), in mammalian cells (Gurer-Orhan, 2006;Matayatsuk et al, 2007) and vegetables (Rodgers et al, 2002). For example, in Vigna radiata phenylalanine tRNA synthetase catalyzes also up to 25% of m-tyrosine instead of phenylalanine (Rodgers et al, 2002).…”
Section: Meta-tyrosinementioning
confidence: 99%